A Mechanistic Investigation of the Visible‐Light Photocatalytic Trifluoromethylation of Heterocycles Using CF3I in Flow. Issue 35 (22nd July 2016) - Su, Yuanhai; Kuijpers, Koen P. L.; König, Niels; Shang, Minjing; Hessel, Volker; Noël, Timothy
Abstract: Photocatalytic radical trifluoromethylation strategies have impacted the synthesis of trifluoromethyl‐containing molecules. However, mechanistic aspects concerning such transformations remain poorly understood. Here, we describe in detail the mechanism of the visible‐light photocatalytic trifluoromethylation of N ‐methylpyrrole with gaseous CF3 I in flow. The use of continuous‐flow microreactor technology allowed for the determination of different important parameters with high precision (e.g., photon flux, quantum yield, reaction rate constants) and for the handling of CF3 I in a convenient manner. Our data indicates that the reaction occurs through a reductive quenching mechanism and that there is no radical chain process present. Abstract : Precision and safety in flow : The mechanism for the visible‐light‐induced photocatalytic trifluoromethylation of N ‐methylpyrrole with CF3 I has been elucidated. The use of continuous‐flow microreactor technology allowed for the determination of different important parameters with high precision as well as the handling of CF3 I in a straightforward manner.